2018
DOI: 10.4269/ajtmh.17-0988
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Risk Factors of Antimicrobial Use in Children Less Than 5 Years of Age with Diarrheal Illness in Rural Bangladesh

Abstract: Antimicrobial overuse contributes to antimicrobial resistance. Empiric use of antimicrobials for diarrheal illness is warranted only in a minority of cases, because of its self-limiting nature and multifactorial etiology. This study aims to describe the factors contributing to antimicrobial overuse for diarrheal disease among children less than 5 years of age in rural Bangladesh. A total of 3,570 children less than 5 years of age presenting with diarrhea in a tertiary level hospital were enrolled in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…This finding is consistent with multiple other studies and known mechanisms of acquired resistance, demonstrating that patient antibiotic use places selective pressure towards MDR (Das et al, 2013). Antibiotic use was common, with nearly one-third of subjects reporting antibiotic use prior to hospital presentation, consistent with a study that found 39% home (non-prescription) antibiotic use among young children in rural Bangladesh (Mirzapur) (Ahmed et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with multiple other studies and known mechanisms of acquired resistance, demonstrating that patient antibiotic use places selective pressure towards MDR (Das et al, 2013). Antibiotic use was common, with nearly one-third of subjects reporting antibiotic use prior to hospital presentation, consistent with a study that found 39% home (non-prescription) antibiotic use among young children in rural Bangladesh (Mirzapur) (Ahmed et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Health sector (combined by 'OR') (b) Geographic location (combined by 'OR') (c) and/or its indiscriminate use [17]. Studies reveal two or more antimicrobials to be commonly prescribed at a time in Bangladesh [14,15,18,19,20,22,30,31], and more antimicrobials to be prescribed in hospital settings compared to community settings [21]. Prescribing antibiotics without laboratory tests was quite common in Bangladesh due to reported lack of testing facilities [18,19,22].…”
Section: Amr (Combined By 'Or') (A)mentioning
confidence: 99%
“…Drug shops fill an important gap in healthcare infrastructure in Bangladesh and are reported to be the preferred first point of contact for most of the population because of the low cost, long opening hours and wide geographic spread [15, 17]. In a recent study, Ahmed et al [18] found that among children presenting at a tertiary hospital with diarrhoea, of those who had already taken antibiotics at home only 6% had been prescribed by a qualified provider. One study observing practice in 75 drug shops found that antibiotics were the highest selling medicine [13].…”
Section: Introductionmentioning
confidence: 99%